Radiation dosimetry in cell biology: comparison of calculated and measured absorbed dose for a range of culture vessels and clinical beam qualities. (1st February 2018) - Claridge Mackonis, Elizabeth; Hammond, Lauren; Esteves, Ana I. S.; Suchowerska, Natalka
Abstract: Purpose: Cell culture studies are frequently used to evaluate the effects of cancer treatments such as radiotherapy, hormone therapy, chemotherapy, nanoparticle enhancement, and to determine any synergies between the treatments. To achieve valid results, the absorbed dose of each therapy needs to be well known and controlled. In this study, we aim to determine the uncertainty associated with radiation exposure in different experimental conditions. Materials and methods: We have performed an in-depth evaluation of the absorbed dose and dose distribution that would be delivered to a cell sample when cultivated in a number of the more popular designs of culture vessels. We focus on exposure to two beam types: a kilovoltage x-ray beam and a megavoltage photon beam, both of which are routinely used to treat cancer patients in the clinical environment. Conclusions: Our results identify large variations of up to 16% in the absorbed dose across multi-well culture plates, which if ignored in radiobiological experiments, have the potential to lead to erroneous conclusions.